2011
DOI: 10.5588/ijtld.10.0558
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to isoniazid preventive therapy in children exposed to tuberculosis: a prospective study from Guinea-Bissau

Abstract: Overall adherence to IPT was better than previously reported from TB-endemic areas, with 76% of the children completing at least 6 months of treatment, with more than 80% adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 14 publications
3
34
2
3
Order By: Relevance
“…In our study, in both age groups the strongest risk factor for non‐completion of IPT was being contact of an index case with treatment outcome other than success. This could be a spurious finding related to index case and contact moving to a new address, which was a frequent cause of not completing contact evaluation in a study in Guinea Bissau and elsewhere too . Yet, competing priorities in the household, or other factors impacting on discontinuation of TB care in the household, such as substance abuse, could also explain this .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, in both age groups the strongest risk factor for non‐completion of IPT was being contact of an index case with treatment outcome other than success. This could be a spurious finding related to index case and contact moving to a new address, which was a frequent cause of not completing contact evaluation in a study in Guinea Bissau and elsewhere too . Yet, competing priorities in the household, or other factors impacting on discontinuation of TB care in the household, such as substance abuse, could also explain this .…”
Section: Discussionmentioning
confidence: 99%
“…However, as in our study, adherence to therapy was poor in settings where the disease is endemic (range: 15 to 76%). 6,7,[34][35][36][37] In our study, poor staff knowledge of isoniazid preventive therapy and poor compliance with guidelines were found to be barriers to the initiation of therapy. Similar barriers have been reported in other countries: in India, health-care workers reported that unclear guidelines on child contact management inhibited their ability to implement therapy; 38 in Thailand, doctors were reluctant to initiate therapy due to concerns about isoniazid toxicity and resistance; 22 in Australia, doctors actively advised patients not to use isoniazid preventive therapy; 34 in the United States of America, medical graduates did not believe isoniazid preventive therapy was protective against disease progression; 39 and, in Malawi, health-care workers felt that screening child contacts by chest radiography was not worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Previously we presented a public health evaluation framework that involved situational, gap and options analyses and that could be used to identify problem areas and to develop appropriate multi-targeted solutions. 10 In this paper we present the findings of the first two stages of a public health evaluation carried out using this framework in Bandung, West Java, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown in Guinea Bissau that adherence to IPT can be quite high 28 and that IPT in children in households with a recent case of TB lowers mortality. 29 However, a recent cluster randomized trial among 78 744 miners of three gold-mining companies in South Africa showed that IPT had only a short-lasting effect on overall TB incidence in this high-risk population with a high HIV prevalence.…”
Section: Preventive Therapy Of Latent Tuberculosismentioning
confidence: 97%